2012
DOI: 10.1002/chem.201200359
|View full text |Cite
|
Sign up to set email alerts
|

Walking Metals in d8⋅⋅⋅d8 Hetero‐bimetallic Complexes: An Original Dynamic Phenomenon

Abstract: In the course of our investigations on polymetallic complexes derived from 1,3-bis(thiophosphinoyl)indene (Ind(Ph(2)P=S)(2)), we observed original fluxional behavior and report herein a joint experimental/computational study of this dynamic process. Starting from the indenylidene chloropalladate species [Pd{Ind(Ph(2) P=S)(2)}Cl](-) (1), the new Pd(II)···Rh(I) hetero-bimetallic pincer complex [PdCl{Ind(Ph(2) P=S)(2)}Rh(nbd)] (2; nbd=2,5-norbornadiene) was prepared. X-ray crystallography and DFT calculations sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 69 publications
1
20
0
Order By: Relevance
“…Likewise, Nebra et al. observed the shift of a rhodium fragment between the arms of a bimetallic (1,3‐bis(thiophosphinoyl)indenyl)palladium complex across the ligand π system 16…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Likewise, Nebra et al. observed the shift of a rhodium fragment between the arms of a bimetallic (1,3‐bis(thiophosphinoyl)indenyl)palladium complex across the ligand π system 16…”
Section: Introductionmentioning
confidence: 95%
“…[15] Likewise, Nebra et al observed the shift of ar hodiumf ragment between the arms of ab imetallic (1,3-bis-(thiophosphinoyl)indenyl)palladium complex across the ligand p system. [16] One of the questionst hat remain is whether the reactiono f [Pd(PEt 3 ) 4 ]w ith halogenated substrates will reflect that of platinum or nickel;w ill the rate-determining step be similar to the platinum or nickel system and can we control the selectivity of the reaction? In this study,w eobserved that h 2 -coordination of [Pd(PEt 3 ) 2 ]t oaC =Co raC Cm oiety is kinetically favored and followed by arate-determining aryl halide bond activation.…”
Section: Introductionmentioning
confidence: 99%
“…Metal–arene interactions and many metal complexes exhibiting fluxional behavior have been studied for decades including seminal studies by the late Basolo in the 1960s. The motivation behind those fundamental studies is often to gain mechanistic insight, which, in turn, might lead to obtaining more efficient and selective synthetically relevant carbon–carbon coupling reactions. However, direct mechanistic studies are often hampered by short-living intermediates, and therefore, advanced computational methods have provided much valuable information.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the (SCS) Pd complex, the Lewis acid additive may interact with the electron-rich indenediide motif as well as the sulfur atoms and thereby interfere with the Pd–ligand cooperativity. 19 A series of triflate salts were evaluated as LA additives to [(SCS)Pd] 2 in the cyclization of the β-keto,ester 2a in 4/1 chloroform/HFIP as solvent. Initial screenings were performed at 60 °C with 1 mol% Pd and 20 mol% LA (Fig.…”
Section: Resultsmentioning
confidence: 99%